Characteristics of Soil DOM and Its Effect on the Transformation of Potentially Toxic Elements (PTE) Forms under Organic Fertilizer Return Conditions - Hongwei Pan; Lili Shi; Xin Liu; Hongjun Lei; Jie Yu; Guang Yang (Agronomy, 2023)
In order to explore the effects of the composition and structure of soil’s dissolved organic matter (DOM) and its electron transfer capacity (ETC) on the bioavailability of the potential toxic elements chromium (Cr), lead (Pb) and cadmium (Cd) after the application of decomposed pig manure organic fertilizer, three-dimensional fluorescence spectroscopy (3D-EEMs), parallel factor analysis (PARAFAC) and electrochemical methods were used to analyze the composition characteristics of DOM in soil solution and the changes in the ETC, and the dynamic relationship between the relative content of DOM, ETC and various forms of potential toxic elements was explored by means of a Pearson correlation analysis and redundancy analysis (RDA). Among them, Cr, Pb and Cd were the elements with significant biological toxicity in farmland soil. The results indicated the following: (1) The soil DOM before and after returning the organic fertilizer to the field contained four components: UV and UVA humic-like (C1), tryptophan-like and UVA humic-like (C2), Exogenous and visible humic-like (C3) and tyrosine-like (C4). Humus-like was the main component. (2) After applying organic fertilizer, the relative contents of the DOM humus and tyrosine-like components in the soil increased by 8% and 8.73%, respectively. In this process, the DOM electron-accepting capacity (EAC) and electron-donating capacity (EDC) increased by 39.98% and 27.91%, respectively. (3) The humic-like fraction showed a highly significant positive correlation with ETC (p < 0.01), and the tyrosine-like fraction showed a significant negative correlation with ETC (p < 0.05). (4) The humus-like substance and ETC were positively correlated with the total amount, reducible state and oxidizable state of the potential toxic elements and negatively correlated with the weak acid extracted state and residue state; this showed that the humus-like components and ETC were more helpful for the transformation of the weak acid extracted state to the reducible state, oxidizable state and residue state in the interaction between the DOM components and Cr, Pb and Cd. In summary, the reasonable application of organic fertilizer could improve the relative content of DOM and ETC in soil, inhibit the biological toxicity of potential toxic elements in soil and provide a theoretical basis for the safe use of organic fertilizer.